Molecular identification of Ancylostoma species from dogs and an assessment of zoonotic risk in low-income households, São Paulo State, Brazil - Oliveira-Arbex, A. P. [UNESP]; David, E. B. [UNESP]; Oliveira-Sequeira, T. C.G. [UNESP]; Katagiri, S.; Coradi, S. T.; Guimarães, S. [UNESP] (My University, 2017)
Hookworm infection stands out for its worldwide distribution and for its veterinary and public health relevance. Based on copromicroscopic examinations and polymerase chain reaction (PCR) amplification of the ITS1-5.8S-ITS2 region, we assessed, respectively, the prevalence of intestinal parasites and the identification of canine hookworm species in faeces recovered from 278 dogs living in households of an inland municipality of São Paulo State, Brazil. Intestinal parasites were found in 67.3% of dogs and hookworm infection was found at the highest prevalence rate (56.6%), followed by Toxocara canis (11.9%), Isospora spp. (11.9%), Giardia spp. (5.8%), Sarcocystis spp. (4.0%), 'Hammondia-like' (1.4%), Dipylidium caninum (1.1%) and Trichuris vulpis (0.7%). Of 158 samples positive for hookworm eggs, 106 (67.1%) were amplified by PCR and, of those, 88 (55.7%) were successfully sequenced for species identification. Single infections with Ancylostoma caninum and Ancylostoma braziliense were recorded in 61.4% and 12.5%, respectively, and mixed infections were found in 26.1%. The nucleotide sequences of both species showed high identity rates (98-100%) when compared with reference sequences. Although A. caninum was the most prevalent hookworm in the dogs assessed, the occurrence of both A. caninum and A. braziliense in single and/or mixed infections poses a potential risk for the local population in a low-income area, especially children, to acquire cutaneous larva migrans (CLM).